(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2026)
The paper analyzes the economic policies of Mauricio Macri’s government (2015–2019), characterized by a neoliberal orientation subordinated to international financial interests. In a global context of geopolitical reconfiguration and debt recommendations from multilateral organizations, Argentina adopted measures such as the devaluation of the peso, the liberalization of the exchange rate, trade liberalization, the elimination of export taxes, and the deregulation of the energy sector. These decisions favored exporting sectors and large economic groups, replicating historical schemes applied during the Military Regime and the Menem administration. The agreement with the vulture funds, the issuance of public bonds, and the placement of LEBACs at high rates generated a speculative cycle that culminated in a debt overhang crisis. The current account was in deficit throughout the period, and capital flight exceeded 86 billion dollars. In 2018, faced with the exhaustion of the model, the government turned to the IMF, obtaining the largest loan in its history (44.128 billion dollars), without a formal assessment of repayment capacity and in violation of Article VI of the IMF’s Articles of Agreement, according to the General Audit Office of the Nation (AGN, 2023). The article documents the deterioration of social indicators: the increase in poverty, homelessness, inequality (Gini index), and unemployment. The paper reconstructs the evolution of public and private debt, the formation of external assets, the 2018 crisis, and the 2019 default, showing that borrowing was not directed toward infrastructure or development, but rather to financing the external deficit and speculation. It concludes that Macri’s policies consolidated a model of structural dependence, distributive regression, and financial subordination, without improvements in productive capacities or economic development.